Odour Emission From Palm Oil Mill With Different Effluent Treatment System - Merzuki, Muhammad Yusof (Universiti Sains Malaysia, 2017)
Odours caused by Palm Oil Mill operations have become a major environmental issue in the Palm Oil Mill industry in Malaysia. Effluent pond is the major source of odours. It is assumed that the odour emission from ponds are mainly driven by pond loading rate. This undesirable odour will not only affect the air quality concern but also the surrounding residential and institutional area. Therefore, the application of pond cover and tank digester had been implement to remove the odour from palm oil mill anaerobic pond. Pond cover and tank digester is widely used over the world in dealing with odour problems but the use of this system in Malaysia is still low, especially for Palm Oil Mill. In this study, three different Palm Oil Mill had been choose open pond, covered pond and tank digester to compare the odours emission from this three different system and to identify odour limit for palm oil mill effluent. Odour assessment was performed on site, using the SM-100 In-field olfactometer next to the anaerobic pond, anaerobic covered lagoon and anaerobic tank digesters. In addition to in-field odour assessments, flux hood and vacuum chamber being used for odour sampling at the cooling pond and sample had been send to laboratory for dynamic olfactometry analysis. Ammonia test and hydrogen sulfide concentration were also done on odour sampling sample to identify amount of ammonia and hydrogen sulfide had been released to atmosphere. POME sample were also being collected at this three cooling pond to identify ammonia, hydrogen sulphide and total solid. Based on the result, the odour limits for palm oil mill effluent is 57,000 OU/m³. Average of odour emission from uncovered lagoon is 3387 OU/m³, covered lagoon is 185 OU/m3, and for tank digester is 4.0 OU/m3. Total reduction of odour emission when using the covered lagoon is about 95% and 99% when using the tank digester. Therefore, by using cover and tank di